1997
DOI: 10.1023/a:1006847630347
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Immunologic and occupational aspects of the susceptible population exposed to Histoplasma capsulatum, the causative agent of histoplasmosis were analyzed in the Mexican State of Guerrero. Three areas were studied, Juxtlahuaca, Olinala, and Coyuca; in the first two, their populations refer contact with bat guano and/or avian excreta, which contain nutrients for fungal growth, while the Coyuca population referred no contact with the above mentioned excreta. Previous infection with H. capsulatum was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…[15] Although non-Hodgkin lymphoma is more common in whites than blacks and genetic differences in susceptibility to histoplasmosis have been reported, these factors are unlikely to account for a difference of this magnitude. [16, 17] Residential areas in the Memphis metropolitan area had racial dissimilarity indices of 32-66% over the study period suggesting that, as previous studies have illustrated, differences in exposure or the intensity of exposure to infectious conidia in the environment at the neighborhood level might contribute to higher rates of histoplasmosis in some racial and ethnic groups. [16, 18]…”
Section: Discussionmentioning
confidence: 95%
“…[15] Although non-Hodgkin lymphoma is more common in whites than blacks and genetic differences in susceptibility to histoplasmosis have been reported, these factors are unlikely to account for a difference of this magnitude. [16, 17] Residential areas in the Memphis metropolitan area had racial dissimilarity indices of 32-66% over the study period suggesting that, as previous studies have illustrated, differences in exposure or the intensity of exposure to infectious conidia in the environment at the neighborhood level might contribute to higher rates of histoplasmosis in some racial and ethnic groups. [16, 18]…”
Section: Discussionmentioning
confidence: 95%
“…Outside of outbreaks, occupational associations with histoplasma exposure have been estimated using skin testing. Such studies have demonstrated higher rates of histoplamin reactivity associated with various occupations including poultry workers [29, 33], cave tourist-guides [29], guano collectors [29], and farmers [34]. To our knowledge, our study is the first to demonstrate association between the granulomatous sequelae of histoplasma exposure and occupation.…”
Section: Discussionmentioning
confidence: 51%
“…One study demonstrated higher gene frequencies of HLA-B22 and HLA-B17 observed in areas of higher rates of histoplasmin skin reactivity [29]. Numbers in this study were limited to fewer than 30 subjects per area, and association with histoplasmosis was speculative.…”
Section: Discussionmentioning
confidence: 84%
“…Patients at high risk for reactivating latent infection and developing disseminated histoplasmosis are those chronically receiving corticosteroids or chemotherapy, those receiving anti-cytokine therapies (tumor necrosis factor alpha or gamma interferons antagonists), individuals who have received solid organ transplantation, and patients with advanced HIV infection [63,67]. Additional risk factors for histoplasmosis include smoking [69], COPD [70], extreme ages (infants younger than 2 years old, elderly older than 50 years old) [71], and genetics deficiencies (IFN-γ receptor 1 deficiency or histocompatibility complex haplotypes) [72,73].…”
Section: Hostmentioning
confidence: 99%